Actor–Partner Effects of Personality Traits and Psychological Flexibility on Psychological Distress Among Couples Coping with Cancer - Leegal Bar-Moshe-Lavi; Nimrod Hertz-Palmor; Keren Sella-Shalom; Michal Braun; Noam Pizem; Einat Shacham-Shmueli; Eshkol Rafaeli; Ilanit Hasson-Ohayon (Behavioral Sciences)
In this study, we applied the actor–partner interdependence model (APIM) to explore the associations between personality traits (Big Five) and psychological flexibility, on the one hand, and depression and anxiety, on the other hand, among patients with cancer and their spouses. Method: Forty-six patient—spouse dyads (N = 92) completed the anxiety and depression scales from the Patient-Reported Outcomes Measurement Information System (PROMIS), the ten-item personality inventory (TIPI), and the psychological flexibility scale (AAQ-2). Multilevel APIM models, adjusted for multiple testing, showed that neuroticism and psychological flexibility had actor effects on patients’ depression and anxiety. Furthermore, neuroticism had actor effects on spouses’ depression and anxiety, and agreeableness had actor effects on spouses’ anxiety. In addition, patients’ psychological flexibility and neuroticism had partner effects on spouses’ depression. Conclusion: Being psychologically flexible but emotionally stable is important for one’s own and one’s partner’s psychological outcomes in the context of dyadic coping with cancer. Implications include informing couples’ therapists in the context of psycho-oncology on the importance of considering personality traits and improving psychological flexibility.